Oman-Saudi Arabia to open first ever road link - Mukrashi, Fahad al- (2015)
‘Engineering marvel’ stretches 680km through the moving sands of the Empty Quarter. Watch the video
Keywords: Relations -- Oman -- Arabie Saoudite

The Buraimi Affair: Oil Prospecting and Drawing the Frontiers of Saudi Arabia - Morton, Michael Quentin (Asian Affairs, 2015)
Keywords: Relations -- Oman -- Arabie Saoudite